Implementation of Binjai Mayor Regulation Number 9 of 2022 Concerning the Protection of Women and Children from Violence - Rizkya, Salsa; Batubara, Beby Masitho; Siregar, Nina Siti Salmaniah (Pusat Studi Pembangunan dan Pemberdayaan, 2025)
Binjai Mayor Regulation Number 9 of 2022 concerning the Protection of Women and Children from Violence is a strategic policy to overcome the high rate of violence against these vulnerable groups. This research aims to analyze the implementation of policies, the challenges faced, and the necessary improvement measures. The research uses a descriptive qualitative approach with in-depth interviews, observations, and documentation studies. The subjects of the study include government officials, field officers, non-governmental organizations, and victims of violence. The results of the study show that the implementation of the policy has resulted in several achievements, such as the formation of integrated services for victims of violence, increasing public awareness through educational campaigns, and cross-sector cooperation for case handling. However, the implementation of this policy has not run optimally due to various obstacles, such as limited human resources and budgets, low public awareness, patriarchal cultural barriers, and ineffective coordination between institutions. These obstacles have an impact on the slow process of handling cases and the lack of optimal support for victims of violence. Therefore, this study recommends increased budget allocation, professional training, strengthening cross-agency coordination mechanisms, and more intensive public campaigns to change cultural norms that support violence. In conclusion, although these policies have had a positive impact, further efforts are needed to improve their effectiveness. With integrated strategic steps, this policy has the potential to become a stronger instrument in protecting women and children from violence in Binjai City.